Useful Knowledge for Social Work Practice - Jeanne Marsh (Social Work and Society, 2006)
Social workers have a long-standing interest in the relation of knowledge and practice. Both the tasks of practice and the knowledge used to accomplish these tasks are defining characteristics of any profession. They are the basis by which professions differentiate themselves from one another and the means by which they legitimate their activities to the larger society and culture. Theorists and researchers of knowledge utilization have identified it as having both conceptual and instrumental aspects. To better understand knowledge utilization in the field of social work, a group of social work practitioners were asked to reflect on the utility of various types of formal information and knowledge and sources of that knowledge. Practitioner respondents expressed appreciation for theoretical knowledge, but gave highest utility ratings to knowledge that helps them solve problems they confront every day in practice, i.e., information about a social problem or information about the effectiveness of a particular social work intervention. Younger practitioners were more enthusiastic than older practitioners about the utility of formal knowledge.